2018
DOI: 10.1002/phar.2149
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Use of Novel Biomarkers to Improve the Safety of Renally Eliminated and Nephrotoxic Medications

Abstract: Over the last decade, the discovery of novel renal biomarkers and research on their use to improve medication effectiveness and safety has expanded considerably. Pharmacists are uniquely positioned to leverage this new technology for renal assessment to improve medication dosing and monitoring. Serum cystatin C is a relatively new, inexpensive, functional renal biomarker that responds more quickly to changing renal function than creatinine and is not meaningfully affected by age, sex, skeletal muscle mass, die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 55 publications
(137 reference statements)
0
34
0
1
Order By: Relevance
“…Development of drug-specific algorithms are needed. 48 We recommend that for drugs with narrow therapeutic indices (eg, chemotherapeutics), high observed interpatient variability in drug levels (eg, blactams), or in high-risk populations (eg, elderly, critically ill), rigorous pharmacokinetic studies be performed and reported using standardized criteria. 46 Results from these studies could inform development of user-friendly dosing tools that then should be tested in pragmatic clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Development of drug-specific algorithms are needed. 48 We recommend that for drugs with narrow therapeutic indices (eg, chemotherapeutics), high observed interpatient variability in drug levels (eg, blactams), or in high-risk populations (eg, elderly, critically ill), rigorous pharmacokinetic studies be performed and reported using standardized criteria. 46 Results from these studies could inform development of user-friendly dosing tools that then should be tested in pragmatic clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, renal function may still be dynamic during the collection and assessment time. Novel renal biomarkers such as cystatin C have recently been proposed as alternative and potentially more accurate compounds to characterize renal function compared to S cr concentration . Alternatively, use of therapeutic drug monitoring for β‐lactams and other agents may be a means to assess clearance while ensuring adequate exposure .…”
Section: Alternative Approaches To Estimating Renal Function In Patiementioning
confidence: 99%
“…Novel renal biomarkers such as cystatin C have recently been proposed as alternative and potentially more accurate compounds to characterize renal function compared to S cr concentration. 20 Alternatively, use of therapeutic drug monitoring for b-lactams and other agents may be a means to assess clearance while ensuring adequate exposure. 21 However, neither biomarker analysis nor therapeutic drug monitoring (for most antibiotics) is performed routinely, and best practices will need to be well defined before widespread implementation into clinical practice.…”
Section: Alternative Approaches To Estimating Renal Function In Patiementioning
confidence: 99%
“…Recently developed functional and damage biomarkers as possible early warning markers for AKI and, more specifically, drug‐associated AKI are gaining attention . The use of biomarkers in clinical practice is described by Barreto and colleagues . Drug‐associated QT c ‐interval prolongation is another safety concern.…”
mentioning
confidence: 99%
“…20 The use of biomarkers in clinical practice is described by Barreto and colleagues. 21 Drug-associated QT c -interval prolongation is another safety concern. Muensterman and colleagues review the literature on the use of predictive analytics to assist with early warning of patients at risk for QT c -interval prolongation.…”
mentioning
confidence: 99%